Էլդա Գրինի կյանքն ու ստեղծագործական ուղին - Լիանա Օհանյան (ՀՀ ԳԱԱ հրատ.)
Современная армянская писательница, психолог и судебный эксперт Эльда Грин (1928-2016) – одна из тех авторов, которые тонко отображают современную жизнь, проникая во внутренний мир каждого героя, находя новые и интересные краски. Ее художественный стиль лаконичен, наполнен гуманистическими элементами. The contemporary Armenian writer, psychologist and judicial expert Elda Grin (1928-2016) is one of those overbusy and multitalented authors. She with mild transitions and as an unerring considerate psychologist depicts today’s life penetrating into the inner world of each hero, there finding new and interesting nuances.
Keywords: Biography; Language and Literature